Language Use: Code Mixing, Code Switching, Borrowing, Pidginization, and Creolization - Dewi, Komang Trisna (Yavana Bhasha : Journal of English Language Education, 2021)
This study was conducted to gather sufficient information on the language use: code mixing, code switching, borrowing, pidginization, and creolization. The method used in this study is through a literature study that collects several previous studies to answer about code mixing, code switching, borrowing, pidginization, and creolization purposes. The results of this study that code can be a variety related to the element of language like sentence, clause, phrase and word which have the limitation because the code which is chosen by the speaker based on his/her necessity in communicating. CodeMixing is the mix of code from two languages or more in some content of conversation in form of a sentence, while Code-Switching defined as a term which is used to indicate exchange of two or more languages, varieties of language, and can be also an exchange in style. Moreover, Borrowing is the process of importing linguistic items from one linguistic system into another, a process that occurs any time two cultures are in contact over a period of time. Furthermore, Pidginization is a simplification of code of language which has arisen as the result of contact between people of different languages usually formed a mixing of the languages. When pidgin develops to creole, it is described as creolization. Creole is a pidgin which is modified and appropriated in its structure and vocabulary.